Micro/nanoplastics: a potential threat to crops - Lulu Sun; Xiaoyun Wang; Hanqing Zhao; Zhenyu Wang; Yifan Zhao; Huang Huang; Rui Yang; Shaohui Wang; Wenchao Zhao (Vegetable Research)
The distribution of micro/nanoplastics in soil and water environments is a potential agricultural threat. Since micro/nanoplastics are a new and highly concerning contaminant, in recent years research on micro/nanoplastics has rapidly increased. Here, we review recent scientific papers on micro/nanoplastics in agricultural systems, including micro/nanoplastic sources, microplastic adsorption, nanoplastic absorption, micro/nanoplastic effects on crops, and micro/nanoplastic detection and removal methods. There is very little information available concerning nanoplastic transport in planta; therefore, more research is needed to gain a better understanding of how micro/nanoplastic particles are transported. We also discuss the accumulation of micro/nanoplastics in crops as a potential threat to food safety. Finally, we propose future micro/nanoplastic research directions.